Природа и люди Украины в представлениях и художественном мире Максима Горького 1890 1910-х годов - Бєлова, Тамара Дмитрівна; Byelova, Т. (Східноєвропейський національний університет імені Лесі Українки, 2013)
В статье на материале рассказов «Вывод», «Покойник» и очерка «М. М. Коцюбинский» рассматривается одна из характерных особенностей мировосприятия и творческой индивидуальности Максима Горького − гуманиста, человека мира, исповедующего идеи целостности славянства, единой планетарной культуры, самоценность и красоту человеческой жизни как уникального явления в мире природы.In this article on the material of the novels «Deduction», «The deceased» and essay «M. M. Kotsu¬bynsky» we considered one of characteristic peculiarities of Maksim Gorkyj’s world-view and creative individual. This writer proclaimed ideas of entirety of Slavs, of united planetary culture, of value and beauty of human life as unique phenomenon in the world of nature.
Nature and People of Ukraine in Notions and Artistic World of Maksim Gorkyj in 1890−1910-th
Keywords: Максим Горький; Михайло Коцюбинський; український пейзаж; люди; краса і потворність; філософія життя; звичаї; культура; Maksim Gorkyj; Myhajlo Kotsyubynsky; Ukraine scenery; people; beauty and ugliness; philosophy of life; customs; culture